2012
DOI: 10.1021/jp2116998
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Periodic Mesoporous Organosilicas (PMO-SBA-16): A Support for Immobilization of d-Amino Acid Oxidase and Glutaryl-7-amino Cephalosporanic Acid Acylase Enzymes

Abstract: This study examined the adsorption and stability of D-amino acid oxidase (DAAO) and glutaryl-7-amino cephalosporanic acid acylase (GL-7-ACA acylase) enzymes using two different types of periodic mesoporous organosilicas PMO-SBA-16 synthesized from 1,2-bis(trimethoxysilyl)ethane (BTME) and 1,4-bis(triethoxysilyl)benzene (BTEB). Very high loading, specific enzymatic activities, and stabilities have been reached by proper optimization of mesopore structure and morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The morphologies of the MIP and NIP after removal of template are shown in figure 2 below. The images of the MIP illustrate that the PMO-MIP had almost cubic particle morphology similar to the prepared BTEB-SBA 16 reported by Nohair and his colleagues 15 . Zang and companions concluded that large caged cubic PMO could be prepared easily by using F127 in the presence of acetone or tetrahydrofuran instead of ethanol which is why it is believed that the polymer had large domains of well-ordered cage like mesostructure 16 .…”
Section: Semsupporting
confidence: 76%
“…The morphologies of the MIP and NIP after removal of template are shown in figure 2 below. The images of the MIP illustrate that the PMO-MIP had almost cubic particle morphology similar to the prepared BTEB-SBA 16 reported by Nohair and his colleagues 15 . Zang and companions concluded that large caged cubic PMO could be prepared easily by using F127 in the presence of acetone or tetrahydrofuran instead of ethanol which is why it is believed that the polymer had large domains of well-ordered cage like mesostructure 16 .…”
Section: Semsupporting
confidence: 76%
“…Zhu and coworkers 96 synthesized a novel hierarchical PMO monolith using N,Sbis [3-(triethoxysilyl)propyl]-carbamothioic acid to fabricate a highly efficient enzyme immobilizer. Kaliaguine and co-workers 97 examined the adsorption and stability of D-amino acid oxidase and glutaryl-7-amino cephalosporanic acid acylase using two different types of PMOs: PMO-SBA-16 synthesized from 1,2-bis(trimethoxysilyl)ethane (BTME) and 1,4-bis(triethoxysilyl)benzene. Very high loading (68.8 mg g À1 for D-amino acid oxidase, 51.9 mg g À1 for glutaryl-7-amino cephalosporanic acid acylase), specific enzymatic activities and stabilities were obtained after proper optimization of the mesopore structure and morphology.…”
Section: Pmos For Advanced Applications Ss Park Et Almentioning
confidence: 99%
“…The procedure for immobilization of rGLA on nanoporous materials was performed as follows method Nohair et al [8].…”
Section: Immobilization Of Rgla On Nanomaterialsmentioning
confidence: 99%